THE ROLE OF SOCIAL CHANNELS IN IMPROVING THE COMPETENCE OF HEALTHCARE WORKERS ON SARS-CoV-2 (COVID-19) - Ibadullayeva Sevara Saliybayevna; Ikramova Nargiza Alisher qizi (Modern American Journals, 2025)
This article provides a scientific analysis of the role, significance, and effectiveness of social media—particularly Telegram channels—in enhancing the professional competencies of healthcare workers during the COVID-19 pandemic. It discusses the capacities of the mobile health (m-health) system, mechanisms of distance learning, methods of knowledge assessment through online testing, and the advantages of digital platforms during the pandemic.
Keywords: COVID-19, SARS-CoV-2, medical education, m-health, social networks, Telegram channel, distance learning, clinical guidelines.